Alcohol consumption in Mozambique: regular consumption, weekly pattern and binge drinking - Padrão, Patríca (2011)
This study aimed to describe alcohol consumption in Mozambique, discriminating binge drinking behaviour and the weekday variation in drinking patterns, and to quantify the association between socio-demographic characteristics and alcohol intake. A representative sample of 3265 Mozambicans aged 25-64 years was evaluated in 2005 following the World Health Organization Stepwise approach to Chronic Disease Risk Factor Surveillance (STEPS). The consumption of any type of alcoholic beverage, during life and in the previous year, was recorded. Current drinkers were also asked about the number of standard drinks consumed in each day of the previous week. The overall prevalence of current drinking was 28.9% [95% confidence interval (95% CI): 22.6-35.2] in women and 57.7% (95% CI: 49.8-65.7) in men. Forty percent of the current drinkers reported to have had at least one binge drinking occasion in the previous week. The prevalence of current drinking increased with age and education among women and with income among men. No consistent pattern was observed in binge drinking by education in both genders and by annual income among men, but it was significantly less frequent among the more affluent women. Both drinking and binge drinking peaked at the weekend. Knowing the drinking patterns in Mozambique enables the planning of interventions according to the local needs. Future surveys should also include non-adult populations as risk factors for chronic diseases occurs as early as childhood and adolescence, and are associated with increased risk of disease later in life.